1987
DOI: 10.1111/j.1365-2761.1987.tb01061.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of bacteria present within unfertilized salmon eggs at the time of spawning and their possible relation to early lifestage disease

Abstract: The eggs of 30 female chinook salmon, Oncorhynchus tshawytscha (Walbaum), were collected at spawning. Some eggs from each fish were collected for bacteriologic study. Two salmon produced eggs judged to be of poor quality which were not used. The remaining 28 of the 30 groups of eggs were fertilized from a single sperm pool and the eggs incubated in separate groups. Mortality data on the developing salmon were recorded regularly through the twelfth week on feed. Unfertihzed eggs from each group were surface-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…Previously, E psychrophilum has been isolated in milt from mature chinook and coho salmon (Holt 1987). In contrast, neither Sauter et al (1987), studying mature coho salmon, nor Rangdale et al (1996), studying rainbow trout, detected F. psychrophilum in milt. The presence of E psychrophilum in the milt indicates the possibility that male fish may transfer the bacteria to the egg at the time of fertilisation.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, E psychrophilum has been isolated in milt from mature chinook and coho salmon (Holt 1987). In contrast, neither Sauter et al (1987), studying mature coho salmon, nor Rangdale et al (1996), studying rainbow trout, detected F. psychrophilum in milt. The presence of E psychrophilum in the milt indicates the possibility that male fish may transfer the bacteria to the egg at the time of fertilisation.…”
Section: Discussionmentioning
confidence: 95%
“…The latter may thus be rendered so permeable as to result in the loss of cell viability without lysis. Sauter et al (1987) reported the occurrence of a wide range of bacteria in the eggs of chinook salmon Oncorhynchus tshawytscha from a population of highly stressed iisn. T'neir findings are, however, at odds with the results of others who report that the yolk of salmonid eggs and alevins, unlike the egg and alevin surfaces (Bell et al 1969, Yoshimizu et al 1980, Barker et al 1989, are generally bacteria-free (Yoshimizu et al 1980, Evelyn et al 1984a, b, Barker et al 1989, 1991, Lee & Evelyn 1989.…”
Section: Resultsmentioning
confidence: 99%
“…Cells of the bacterium can apparently enter the egg prior to ovulation (Lee & Evelyn 1989) or through the rnicropyle after ovulation, while the egg is in contact with infected coelomic fluid (Evelyn et al 1984a). Other Gram-positive and Gram-negative bacteria that are small enough to pass through the micropylar canal, including the fish pathogens Aeromonas hydrophila, A. salmonicida, and Carnobacterium piscicola (Collins et al 1990) (formerly Lactobacillus piscicola; Hiu et al 1984), also occur in the coelomic fluid of spawning fish (Cone 1982, Evelyn et al 1984a, b, Sauter et al 1987, Barker et al 1989. These bacteria are thus in a position to enter the eggs yet, unlike R. salmoninarum, they appear not to be vertically transmitted.…”
Section: Introductionmentioning
confidence: 99%
“…Although this mortality is probably due to a number of factors, bacteria isolated during egg incubation have been implicated in these deaths in several studies (Barnes et al 1997(Barnes et al , 2005Stephenson et al 2003). Other researchers have also suggested that bacteria may negatively impact egg survival (Sauter et al 1987;Barker et al 1989;Holcomb et al 2005), although this relationship is far from certain (Barker et al 1990;Omnes et al 1993). Soft egg disease, possibly caused by bacteria (Wood 1979;Erdahl 1993), has also been observed in Lake Oahe Chinook Salmon .…”
mentioning
confidence: 99%